Perfil de expressão de genes envolvidos nas vias conônica e não-canônica da WNT no tecido cerebral de pacientes portadores de displasia cortical focal - Xavier, Fernando Antonio Costa (2022)
Focal cortical dysplasias (focal cortical dysplasia, FCD) are a type of malformation of cerebral cortical development. FCD is considered one of the most prevalent forms of refractory epilepsy and the main cause of this pathology in children. Cortical delamination and swollen cells are the main histopathological findings found in the affected tissue. FCD is classified into at least three types with different subtypes, and its differentiation is determined by means of magnetic resonance imaging, where it is possible to observe the areas affected by FCD, allowing, when possible or necessary, surgery to remove the FCD. dysplastic region. The lack of animal and cellular models makes research difficult to understand the pathogenesis of FCD. It is a consensus that the disease has a genetic character, however all the mechanisms involved are not yet fully known. It is known that the expression of proteins such as Wnt and β-catenin may be of great importance for the pathogenesis of DGFs. The alteration in the expression of these proteins has important consequences on cell migration and differentiation, which are definitive processes for the alterations found in dysplasia. The silencing or activation of genes related to FCDs is vital for the establishment of these malformations. The present study evaluated the expression of 84 genes related to the activity of the Wnt/β-catenin pathway, through real-time PCR, comparing patients with FCD to the control group. Several genes of the Wnt pathway were found with increased expression. The expression of β-catenin remained the same as the control, however, some of its transcripts showed increased expression. Wnt genes were increased, along with frizzled receptors and the LRP5 co-receptor. The LRP6 co-receptor remained with the same expression as the control.